Analisis Manajemen Kas dan Manajemen Persediaan Terhadap Kinerja Keuangan Pada Toko Ling Food Kota Makassar - Nurtisa Lestari; Andi Batary Citta; Widiastuti Widiastuti (Jurnal Manajemen Riset Inovasi, 2024)
This research aims to analyze the influence of cash management and inventory management on the financial performance of Ling Food Stores in Makassar City during the 2020-2022 period. The main focus of this research is to evaluate how cash and inventory management contributes to a company's liquidity, profitability and operational efficiency, which are measured through various financial ratios such as Current Ratio, Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), Return on Investment (ROI), and Return on Equity (ROE). The research results show that the Current Ratio in 2020 cannot be calculated due to the absence of short-term liabilities, while in 2021 and 2022 each was recorded at 0.095% and 0.216%, reflecting low liquidity. On the other hand, the decrease in Average Inventory from IDR 754,200 in 2021 to IDR 715,000 in 2022, followed by a significant increase in net profit, shows efficiency in inventory management. The increase in GPM, OPM, NPM, ROI, and ROE ratios from 2020 to 2022 reflects significant improvements in financial performance, indicating that more effective cash and inventory management can improve a company's financial health.